Perancangan Sistem Informasi Akuntansi Penjualan Berbasis Web Pada Ahza Cake Dan Bakery - Fifin Ulyaviana; Dilla Dwi Rahmatin (Journal of Applied Accounting and Business, 2021)
Ahza Cake and Bakery is a small culinary business that sells foods such as donuts, pizza, brownies and other foods. This company still uses manual sales and the marketing reach is still to small. The purpose of this research is to design a web-based sales accounting system. The method of data collection is done by interview, observation and literature study. The data analysis technique uses waterfall development. Programming language using PHP and database using MySQL, and system design using Data Flow Diagrams (DFD). The result of this research is that there is a system currently being developed which is useful for reducing errors in recording sales and the wider marketing reach because the system is designed to display the results of sales records so that they are monitored more quickly, accurately and in detail.